Treatment-induced anogenital melanosis is a very frequent finding in patients with vulvar lichen sclerosus - Thilo Gambichler, MD; Gülgün Erdogan, MD; Sera S. Weyer-Fahlbusch, MD; Laura Susok, MD (International Journal of Women's Dermatology)
Background:. Pigmented lesions such as melanosis have rarely been reported in patients with vulvar lichen sclerosus (VLS) that is typically characterized by hypopigmented lesions. Objective:. We aimed to analyze systematically anogenital melanosis in a large cohort of VLS patients. Methods:. We analyzed the clinical data of 198 female patients with VLS. The anogenital lesions of all patients were professionally photographed in a standardized position and illumination. Severity classification of architectural findings followed an easy-to-use clinical score. A modified Melasma Area and Severity Index and an image analysis software were used to evaluate the area and intensity of pigmentation. Results:. According to the clinical score, 79 (198/39.9%) patients showed grade 1 disease, 78 (198/39.4%) grade 2, 37 (198/18.7%) grade 3, and 4 (198/2%) grade 4 disease. About 111 (56.1%) of the 198 patients had anogenital melanosis with a median modified Melasma Area and Severity Index of 3.6 (0.4–14). Univariate analysis revealed that anogenital melanosis was positively correlated with the use of topical estrogens (P = .0018) and negatively correlated with the use of pulsed high-dose corticosteroids plus low-dose methotrexate (PHDC-LDM, P = .021). On multivariable analysis, the use of topical hormone therapy turned out to be a strong independent predictor for the presence of anogenital melanosis (odds ratio: 4.57, 95% confidence interval: 1.66–12.57, P = .0033), whereas PHDC-LDM use was an independent predictor for the absence of anogenital melanosis (odds ratio: 0.35, 95% confidence interval: 0.15–0.84, P = .018). Limitations:. The study includes the retrospective monocentric design. Conclusion:. Anogenital melanosis is a very frequent and so far, under-reported clinical finding in VLS patients. It is likely caused by the use of topical estrogens employed for VLS treatment. In contrast, patients with more severe disease and PHDC-LDM treatment appear to develop less likely anogenital melanosis.